Simple Feasibility Analysis Of Nitrogen-Fixing Cereals Project - Rahmani, Tara Puri Ducha; Kumalawati, Dian Aruni; Tyas, Dian Ayuning; Armanda, Dian Triastari; Rusmadi, Rusmadi (Al-Hayat: Journal of Biology and Applied Biology, 2020)
Nitrogen does not directly have advantages in human physiology system, but it holds one of the most critical roles in plants’ life cycle and productivity. Even though Nitrogen is the most abundant elements in the atmosphere, it is also the most deficient essential nutrients in plants. The proposed idea of the nitrogen-fixing GM crops, particularly wheat, is aimed to overcome those stated cons of the traditional diculture and nitrogen fertilizer. This analysis focus on the overview as well as the pro and cons of the genetically modified nitrogen-fixing plants in providing a better agricultural method. The genetically modifying method to generate a nitrogen-fixing non-legumes carries a significant chance of failure results and hindrance. The multilevel implication occurs when we need to modify the plants that not normally produce nodules in their roots to form the nodules and to modify the Nitrogen-fixing microbes to live in the nodules of non-legumes, which are not their natural dwelling places.In conclusion, the genetically modified crops project to fix their Nitrogen is feasible, but the difficulties and the funds needed still outweigh the benefits obtained in the future. With all of those limitations, the target goal to erase famine in 2050 just by funding the nitrogen-fixing wheat alone seems to be too high to be reached. The funds and efforts should be better spent on other factors and farming methods.